The Impact of Recurrent Abdominal Pain on Quality of Life in Children: A Narrative Review - Jamilatul Sutjipto; Alpha Athiyyah; Lucky Andriyanto (Indonesian Journal Publisher, 2026)
This study aims to review and summarize the existing literature on the impact of recurrent abdominal pain on quality of life in children. This study employed a narrative literature review approach. Scientific articles were retrieved from PubMed, Scopus, and ScienceDirect using keywords related to recurrent abdominal pain and quality of life in children. Articles published between 2014 and 2024 and relevant to the topic were reviewed narratively to identify key themes concerning the impact of RAP on children’s quality of life. A total of 10 relevant articles were analyzed in this review. Overall, the literature indicates that children with recurrent abdominal pain experience a lower quality of life compared to healthy children, particularly in the emotional and physical functioning domains. Impairments in school and social functioning were also consistently reported across studies. Psychosocial factors, such as anxiety and depression, frequently emerged as important determinants of reduced quality of life. The reviewed literature demonstrates that recurrent abdominal pain has a multidimensional impact on children’s quality of life. Therefore, the management of RAP should adopt a holistic approach that addresses not only physical aspects but also the psychological and social well-being of the child.